Художня реалізація трагічного в поемі "село в безодні" Ігоря Качуровського - Крупка, В. (Філологічний дискурс, 2018)
Висвітлено особливості художньої реалізації проблеми голодомору
у творчості Ігоря Качуровського і представників української діаспори,
зокрема з’ясовано природу трагічного і її втілення в поемі «Село в
безодні». Вказано, що твір має яскраво виражений автобіографічний
характер, що увиразнює ідею й трагічний пафос. Вказано, що її
реалізація відбувається як на рівні окремої людини, родини, так і в
розрізі художнього відображення винищення майже покоління
українського народу шляхом політичних репресій, примусового
вивезення українців в Сибір і Далекий Схід, голодомору. The article deals with the peculiarities of the artistic realization of the problem
of famine in the work of Igor Kachurovsky and representatives of the Ukrainian
diaspora, in particular, the nature of the tragic and its embodiment in the poem
«The Village in the Abyss» is clarified. It is indicated that the work has a
pronounced autobiographical character, which permeates the idea and tragic
pathos. Much attention is paid to the spiritual, moral and Christian aspects of
human dignity, which makes it possible to connect the tragic with majestic and
heroic. Through the prism of suffering and horror, the images of female mother, kulak
children and an old grandfather who are doomed to terrifying death in torture by
the hands of servants of the totalitarian regime are characterized. The emphasis is
on conflict, peculiarities of characterization, artistic detail. It is noted that the tragic
problem is revealed polyfunctional: from individual to general, from personal to
national. It is revealed that the tragic is revealed due to the conflict between the
criminal totalitarian system, which acquired special power in the 30th of the 20th
century, and the custom of the people, laid not even for centuries, but for millennia,
of extremely complex existential conflicts of Ukrainian statehood.
It is indicated that its realization takes place both at the level of the individual,
the family, and in the context of the artistic reflection of the extermination of almost
a generation of the Ukrainian people through political repressions, the forced
removal of Ukrainians to Siberia and the Far East, the famine.